2015
DOI: 10.1111/1753-0407.12349
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effects of berberine and its potential effect on the expression of β‐arrestins and intercellular adhesion molecule‐1 and vascular cell adhesion molecule‐1 in streptozocin‐diabetic nephropathy rats

Abstract: Background: Berberine has been shown to exert protective effects against diabetic nephropathy (DN), but the mechanisms involved have not been fully characterized. The aim of the present study was to explore the effects of berberine on the expression of β-arrestins, intercellular cell adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) in DN rat kidneys and investigate the underlying molecular mechanisms. Methods: To create the DN model, rats fed a high-fat and high-glucose diet were inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…A continuously increased expression of ICAM-1 can cause serious damage to the structure and function of tissues and organs (24). Furthermore, ICAM-1 molecules are widely present in the body and are expressed in a variety of hematopoietic and non-hematopoietic cells, which are distributed mainly in various epithelial and endothelial cells, fibroblasts, reticular cells, monocytes, macrophages and lymphocytes (25). In the present study, it was revealed that emodin significantly suppressed ICAM-1 expression in DN model rats.…”
Section: Discussionmentioning
confidence: 99%
“…A continuously increased expression of ICAM-1 can cause serious damage to the structure and function of tissues and organs (24). Furthermore, ICAM-1 molecules are widely present in the body and are expressed in a variety of hematopoietic and non-hematopoietic cells, which are distributed mainly in various epithelial and endothelial cells, fibroblasts, reticular cells, monocytes, macrophages and lymphocytes (25). In the present study, it was revealed that emodin significantly suppressed ICAM-1 expression in DN model rats.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 6, berberine ameliorated renal inflammation and injury in diabetic models [79,83,85,86,90,96]. Underlying mechanisms include inhibition of kidney fibrosis via tumor growth factor (TGF)- signaling suppression and Nrf2 activity enhancement [76,77,80,82,86,91,93,144], suppression of HG-induced mesangial cell proliferation and hypertrophy via suppression of NF-B and AP-1 [81,84,90], and attenuation of ECM accumulation [87], possibly by restoring β-arrestin [88] and E prostanoid receptor 4 (EP4)-Gαs-cAMP signaling pathway [83,85]. In addition, berberine directly protected podocytes from HG-induced injury in vitro [23,94], possibly by inhibiting podocyte apoptosis via AMPK-dependent autophagy induction [92].…”
Section: Kidney Dysfunctionmentioning
confidence: 99%
“…The cell adhesion molecules, ICAM-1and VCAM-1, mediate leukocyte and vascular endothelial cell adhesion, as well as leukocyte activation, thereby triggering a proinflammatory response [27]. Previous studies have shown that ICAM-1 and VCAM-1 expression is closely related to the development of diabetic vascular disease [28]. Also, NF-κB signaling manifests as a deep involvement in the inflammatory process, particularly regarding the regulation of ICAM-1and VCAM-1 expression [29].…”
Section: Discussionmentioning
confidence: 99%